Exploring Indonesian Panic Buyers’ Typologies in Time of Covid-19 Pandemic - Lukitaningsih, Ambar; Hartono, Arif (Jurnal Siasat Bisnis, 2024)
Purpose – This study aims to investigate hitherto unresearched panic buyer (shopper) typologies among Indonesian consumers as a result of the COVID-19 outbreak. In this study, a panic buyer (shopper) is described as a customer who worries about their stock during a pandemic and decides to purchase things in bulk or in greater quantities at the start of the pandemic. Design/methodology/approach – To identify probable groupings of the items, an exploratory factor analysis is carried out using principal component analysis and varimax rotation. Then to identify consumer groups, a two-step cluster analysis was conducted. Lastly, an ANOVA test is run on the whole set of variables to identify differences between the detected clusters in order to validate the cluster solutions. Findings – Five components that served as the foundation for the typology emerged from exploratory factor analysis. Using behaviour and attitude factors including "consumption savers," "adapters reluctant," "preservers of social consciousness," "online shopping shifters," and "all-around adapters," five clusters were then defined. Research limitations/implications – This study contributes significantly to the body of knowledge on consumer behavior during health crises (Covid-19) by putting into context the frantic shoppers that we frequently observe during these situations. It's noteworthy that throughout the epidemic, no panic buyers (shoppers) voiced worry about health problems. Practical implications – This study provides essential practical information for marketing professionals. For instance, it may be necessary to consider research showing that panic buyers (shoppers) tend to be consumption savers during a pandemic when developing a price plan. Originality/value – Despite the fact that there have been many studies on panic behavior during COVID-19, most of them tend to concentrate on medical problems. There are now a few studies that examine several sorts of panic buyers (shoppers) based on their purchasing behaviors and attitudes. By categorizing various categories of panic buyers (shoppers) among 121 decision-makers in families, this study aims to close this literature gap.